2021
DOI: 10.1097/lgt.0000000000000599
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Vulvar Lichen Sclerosus Patients Treated With Long-Term Topical Corticosteroids

Abstract: Objective The aim of the study was to investigate the quality of life in vulvar lichen sclerosus (VLS) patients treated with long-term, individualized topical corticosteroids. Methods A prospective cross-sectional study comparing new pretreatment and long-term treated VLS patients attending a dermatogynecology practice in Sydney, Australia. Participants were invited to complete the Vulvar Quality of Life Index (VQLI). The VQLI scores were compared betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Patients who remain asymptomatic are still at risk of complications including carcinoma 7 . A recently published study has shown that long‐term treatment greatly improves quality of life and reduces risk of scarring 23 . In contrast to European and British guidelines, which recommend treating only active LS during maintenance therapy, 4,8 an Australian study has shown that regular, long‐term, preventative treatment with TCS that achieve objective normality of skin leads to better disease outcomes 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who remain asymptomatic are still at risk of complications including carcinoma 7 . A recently published study has shown that long‐term treatment greatly improves quality of life and reduces risk of scarring 23 . In contrast to European and British guidelines, which recommend treating only active LS during maintenance therapy, 4,8 an Australian study has shown that regular, long‐term, preventative treatment with TCS that achieve objective normality of skin leads to better disease outcomes 22 .…”
Section: Discussionmentioning
confidence: 99%
“…7 A recently published study has shown that long-term treatment greatly improves quality of life and reduces risk of scarring. 23 In contrast to European and British guidelines, which recommend treating only active LS during maintenance therapy, 4,8 an Patients should use preventative TCS treatment regularly despite being asymptomatic. 5 81% A treatment regimen using intermittent or 'as required' TCS to control symptoms only is NOT recommended.…”
Section: Long-term Managementmentioning
confidence: 99%
“…Ethics approval was obtained from the Northern Sydney Local Health District Human Research Ethics Committee. A randomised controlled trial was not conducted, as there is robust evidence indicating that insufficient treatment with TCS can lead to scarring and neoplasia 4,6,7 . Therefore, the authors believe it would be unethical to conduct such a study.…”
Section: Methodsmentioning
confidence: 99%
“…VLS can be highly debilitating if left untreated, as it predominantly manifests with intense vulval pruritus, pain from excoriations and fissuring, as well as dyspareunia, thereby interfering with day‐to‐day activities and negatively impacting on quality of life (QOL) 1,2 . Inadequate treatment also increases the risks of vulval scarring, destruction of vulval architecture and vulval squamous cell carcinoma (vSCC) 3–8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation